Efficacy and tolerability of trabectedin in elderly patients with sarcoma: subgroup analysis from a phase III, randomized controlled study of trabectedin or dacarbazine in patients with advanced liposarcoma or leiomyosarcoma. (2nd August 2018) - Jones, R L; Demetri, G D; Schuetze, S M; Milhem, M; Elias, A; Van Tine, B A; Hamm, J; McCarthy, S; Wang, G; Parekh, T; Knoblauch, R; Hensley, M L; et al.
Abstract: Background: Treatment options for soft tissue sarcoma (STS) patients aged ≥65 years (elderly) can be limited by concerns regarding the increased risk of toxicity associated with standard systemic therapies. Trabectedin has demonstrated improved disease control in a phase III trial (ET743-SAR-3007) of patients with advanced liposarcoma or leiomyosarcoma after failure of anthracycline-based chemotherapy. Since previous retrospective analyses have suggested that trabectedin has similar safety and efficacy outcomes regardless of patient age, we carried out a subgroup analysis of the safety and efficacy observed in elderly patients enrolled in this trial. Patients and methods: Patients were randomized 2 : 1 to trabectedin ( n = 384) or dacarbazine ( n = 193) administered intravenously every-3-weeks. The primary end point was overall survival (OS); secondary end points were progression-free survival (PFS), time-to-progression, objective response rate (ORR), duration of response, symptom severity, and safety. A post hoc analysis was conducted in the elderly patient subgroup. Results: Among 131 (trabectedin = 94; dacarbazine = 37) elderly patients, disease characteristics were well-balanced and consistent with those of the total study population. Treatment exposure was longer in patients treated with trabectedin versus dacarbazine (median four versus two cycles, respectively), with a significantly higher proportion receiving prolonged therapy (≥6 cycles) in the trabectedin arm (43% versus 23%, respectively; P = 0.04). Elderly patients treated with trabectedin showed significantly improved PFS [4.9 versus 1.5 months, respectively; hazard ratio (HR)=0.40; P = 0.0002] but no statistically significant improvement in OS (15.1 versus 8.0 months, respectively; HR = 0.72; P = 0.18) or ORR (9% versus 3%, respectively; P = 0.43). The safety profile for elderly trabectedin-treated patients was comparable to that of the overall trabectedin-treated study population. Conclusions: This subgroup analysis of the elderly population of ET743-SAR-3007 suggests that elderly patients with STS and good performance status can expect clinical benefit from trabectedin similar to that observed in younger patients. Trial registration: www.clinicaltrials.gov, NCT01343277.